Expression of heat shock proteins on the plasma membrane of cancer cells : a potential multi-chaperone complex that mediates migration - Kenyon, Amy (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
Current dogma suggests that the Heat Shock Protein (Hsp) molecular chaperones and associated co-chaperones function primarily within the cell, although growing evidence suggests a role for these proteins on the plasma membrane of cancer cells. Hsp90 does not function independently in vivo, but instead functions with a variety of partner chaperones and co-chaperones, that include Hsp70 and Hsp90/Hsp70 organising protein (Hop), which are thought to regulate ATP hydrolysis and the binding of Hsp90 to its client proteins. Hsp90 on the plasma membrane appears to have distinct roles in pathways leading to cell motility, invasion and metastasis. We hypothesised that Hsp90 on the plasma membrane is present as part of a multi-chaperone complex that participates in the chaperone-assisted folding of client membrane proteins in a manner analogous to the intracellular chaperone complex. This study characterised the membrane expression of Hsp90, Hsp70 and Hop in different cell models of different adhesive and migratory capacity, namely MDA-MB-231 (metastatic adherent breast cancer cell line), MCF-7 (non-metastatic adherent breast cancer cell line), U937 and THP1 (monocytic leukemia suspension cell lines). Membrane expression of the Hsps was analysed using a combination of subcellular fractionation, biotin-streptavidin affinity purification and immunofluorescence. This study provided evidence to suggest that Hsp90, Hsp70 and Hop are membrane associated in MDA-MB-231 and MCF-7 breast cancer cells. Hsp90, Hsp70 and Hop associated with the plasma membrane such that at least part of the protein is located extracellularly. Immunofluorescence analysis showed that Hsp90, Hsp70 and Hop at the leading edge may localize to membrane ruffles in MDA-MB-231 cells, in accordance with the published role of Hsp90 in migration. An increase in this response was seen in cells stimulated to migrate with SDF-1. By immunoprecipitation, we isolated a putative extracellular membrane associated complex containing Hsp90, Hsp70 and Hop. Using soluble Hsp90 and antibodies against membrane associated Hsp90, we suggested roles for soluble extracellular Hsp90 in mediating migration by wound healing assays and inducing actin reorganisation and vinculin-based focal adhesion formation. The effects of extracellular Hsp90 are mediated by signalling through an ERK1/2 dependent pathway. An anti-Hsp90 antibody against an N-terminal epitope in Hsp90 appeared to be able to overcome the death inducing effects of a combination of SDF-1 and AMD3100, while soluble Hsp90 could not overcome this effect. We propose that this study provides preliminary evidence that extracellular Hsp90 functions as part of a multi-chaperone complex that includes Hsp70 and Hop. The extracellular Hsp90 chaperone complex may mediate cell processes such as migration by modulating the conformation of cell surface receptors, leading to downstream signalling.
Keywords: Heat shock proteins; Protein folding; Molecular chaperones; Cancer -- Treatment